2017
DOI: 10.1021/acs.inorgchem.7b00831
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) Bipyridyl Complexes with Cyclometalated NHC Ligands

Abstract: We present the synthesis and characterization of novel cyclometalated ruthenium N-heterocyclic carbene (NHC) complexes of the general formula [Ru(C^C*)(bpy)]PF (bpy = 2,2'-bipyridine), with the C^C* ligand being based on different 1-phenylimidazoles. They were synthesized in a one-pot procedure starting from the corresponding p-cymene NHC complexes [Ru(C^C*)(p-cymene)Cl]. Their structural, spectroscopic, and electrochemical properties were investigated by NMR, X-ray, UV/vis, and CV, as well as density function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 139 publications
(199 reference statements)
3
25
0
Order By: Relevance
“…LEDs, luminescent solar concentrators and related photonic technologies represent other platforms where Cs‐based perovskites can behave as core materials in combination with other recently emerged advanced concepts . In this scenario, Mn 2+ doping is currently considered one of the leading strategies to modify the optical and magnetic functionalities of nanocrystals of various chalcogenide and oxide semiconductors .…”
Section: Caesium‐doped Perovskites In Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…LEDs, luminescent solar concentrators and related photonic technologies represent other platforms where Cs‐based perovskites can behave as core materials in combination with other recently emerged advanced concepts . In this scenario, Mn 2+ doping is currently considered one of the leading strategies to modify the optical and magnetic functionalities of nanocrystals of various chalcogenide and oxide semiconductors .…”
Section: Caesium‐doped Perovskites In Emerging Technologiesmentioning
confidence: 99%
“…LEDs, luminescent solarc oncentrators and related photonic technologiesr epresent other platforms where Cs-based perovskites can behavea sc ore materials in combination with other recently emerged advanced concepts. [244][245][246][247][248][249][250][251][252][253] In this scenario, Mn 2 + doping is currently considered one of the leadings trategies to modify the opticala nd magnetic functionalitieso f nanocrystals of variousc halcogenide ando xide semiconductors. [254] An interesting synergy between these materials chemistry features was proposed by Yuan et al,w ho synthesized as eries of Mn 2 + -doped CsPbCl 3 nanocrystals using reaction temperature and precursor concentration to tune Mn 2 + content up to 14 %.…”
Section: Caesium-doping In Other Perovskite Solar Cell Componentsmentioning
confidence: 99%
“…However, the only examples of its use as C ^ C* cyclometalating NHC ligand have been reported for Ir III complexes from the groups of Mashima and Gong and for Pt II complexes from our group. To the best of our knowledge, no examples of ruthenium complexes with imidazo[1,5‐ a ]‐pyridine‐NHC ligands can be found in the literature, which is why we were –following our investigation of related phenylimidazol‐based complexes – interested in their synthesis, reactivity, and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies show that although by these substituents higher efficient DSCs are possible, their redox irreversibility brings additional instability to the molecule . In this regard, search for the new ligand environments for ruthenium complexes with suitable photophysical properties is critical …”
Section: Introductionmentioning
confidence: 99%
“…[12] In this regard, search for the new ligand environments for ruthenium complexes with suitable photophysical properties is critical. [13][14][15] A tridentate ligand -2,6-bis(quinolone-8-yl)pyridine (dqp), which forms six membered chelating rings with the metal center has recently been under intense scrutiny. [16][17][18][19][20] Abrahamson et al observed that, at room temperature, the homoleptic ruthenium complex [Ru(dqp) 2 ] 2 + with two dqp ligands exhibits an excited state lifetime of 3.0 ms, while its [Ru(tpy) 2 ] 2 + (tpy = 2,2':6',2''-terpyridine) analogue's excited state lifetime is less than 1 ns.…”
Section: Introductionmentioning
confidence: 99%